Evaluasi Kebijakan Rencana Tata Ruang Wilayah Kota Padang Terhadap Alih Fungsi Lahan Hijau Menjadi Kawasan Komersial Di Kecamatan Koto Tangah - Annisa Raudah; Rizki Syafril (Science and Education Journal (SICEDU), 2026)
The conversion of green space into commercial areas in Koto Tangah District continues to rise alongside the urban expansion of Padang City. This situation highlights the need to evaluate the implementation of Padang City’s Spatial Plan (RTRW) policy, which serves as an instrument for regulating land-use. This study aims to evaluate the implementation of the Padang City RTRW policy regarding the conversion of green space into commercial areas in Koto Tangah District, as well as to identify the factors influencing its implementation and the measures taken by the local government. A qualitative approach with a descriptive method was employed. Data were gathered through interviews, observation, and document analysis, and subsequently analyzed using an interactive data analysis model involving data reduction, data display, and conclusion drawing. The results indicate that the implementation of the RTRW policy has not been optimal. This is evidenced by the continued conversion of green space, weak supervision and control of land use, suboptimal coordination among local government agencies, and community participation that is primarily driven by economic interests. Furthermore, development pressures have led to a decline in environmental carrying capacity and increased vulnerability to disasters. Therefore, it is essential to strengthen cross-sectoral coordination, enhance supervision, consistently enforce spatial planning regulations, and optimize community participation to support sustainable regional development.